2002
DOI: 10.1002/acp.806
|View full text |Cite
|
Sign up to set email alerts
|

Attending to the peripheral world while driving

Abstract: Do inexperienced drivers see less of the world when driving? Previous research suggests that participants detect fewer peripheral targets while watching video clips of dynamic hazardous driving scenes due to increases in foveal demand (i.e. the presence of a hazard), increases in peripheral target eccentricity, and the lack of driving experience. The current study aimed to further explore the role of experience as a key factor in the potential narrowing of spatial attention, and the possibility of differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 32 publications
4
81
0
Order By: Relevance
“…Novice drivers have restricted scan patterns (e.g. Crundall and Underwood, 1998), they have longer fixation times on roadrelevant objects (Chapman and Underwood, 1998), reduced peripheral attention, (Crundall et al 2002), a poorer lane maintenance (Land and Horwood, 1995), and are slower to respond to hazards (McKenna and Crick, 1991).…”
Section: Research Aimsmentioning
confidence: 99%
“…Novice drivers have restricted scan patterns (e.g. Crundall and Underwood, 1998), they have longer fixation times on roadrelevant objects (Chapman and Underwood, 1998), reduced peripheral attention, (Crundall et al 2002), a poorer lane maintenance (Land and Horwood, 1995), and are slower to respond to hazards (McKenna and Crick, 1991).…”
Section: Research Aimsmentioning
confidence: 99%
“…Crundall, Underwood, and Chapman (1999) found that the appearance of a hazard reduced the ability of participants to spot peripheral targets. Crundall, Underwood, and Chapman (2002) did note however that more experienced drivers recover more quickly after a sudden reduction in peripheral awareness than a control group of learner drivers. This inattentional blindness for extra-foveal stimuli (Mack & Rock, 1998) occurs when the appearance of a target goes unnoticed by participants, not because the onset of the target is masked in any way, but because attentional resources are devoted elsewhere.…”
Section: Introductionmentioning
confidence: 74%
“…Land & Horwood, 1995), and that inexperienced drivers have reduced peripheral awareness (e.g. Crundall et al, 2002), which taken together suggest that novice drivers may have to foveate lane markings in order to maintain lane position. The results support the hypothesis that novice drivers favour sources of lane maintenance information, even when that information is not required (as no motor interaction was necessary).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral vision has been shown to support a number of driving tasks including lane maintenance, speed estimation (Bhise & Rockwell, 1971), and the detection of abrupt onsets or changes in the periphery such as hazard detection (Crundall, Underwood, & Chapman, 2002). However, the minimum visual field consistent with safe driving has not been determined.…”
Section: Compensation Strategiesmentioning
confidence: 99%